“Cegueira botânica” no ensino: uma revisão bibliográfica das descobertas e perspectivas - Fantin, Mirian Morais Dias (Universidade Federal do Tocantins, 2024)
Botânical blindness is a reality that has to be fought, as plant teaching is important for balance for the entire ecosystem. In this sense, the education professional has increasingly sought strategies to mitigate this reality. Thus, research adopted a qualitative and exploratory approach, using a bibliographic review to analyze and synthesize the main discoveries and perspectives in the literature on “Botânical blindness” The method of this research is a bibliographic review of a qualitative nature with exploratory approach. The results of the bibliographic review of 15 chosen studies reveal the crucial importance of the study of botany not only as an academic component, but as a key to unraveling the mysteries of nature. Botânical blindness is identified as a phenomenon that goes beyond the common difficulty of perceiving plants in daily life, including the lack of recognition of their fundamental importance in the biosphere. Effective strategies to combat this blindness include innovative methods, interdisciplinary approaches and contextualization from childhood, aiming to arouse the interest of individuals. It is therefore concluded that overcoming Botânical blindness not only enriches the understanding of plants, but it also contributes to environmental conservation and addresses contemporary challenges, establishing botany as an essential discipline and connected to daily life.